Reversible functionalization and exfoliation of graphite by a Diels–Alder reaction with furfuryl amine. Issue 27 (10th June 2022) - Torkaman, Najmeh Filvan; Kley, Marina; Bremser, Wolfgang; Wilhelm, René
Abstract : Furfuryl amine-functionalized few-layered graphene was prepared via a mechanochemical process by a [4 + 2] cycloaddition under solvent-free conditions. Abstract : Furfuryl amine-functionalized few-layered graphene was prepared via a mechanochemical process by a [4 + 2] cycloaddition under solvent-free conditions. By employing ball milling, active sites are merged mostly at the edge of the graphene sheets which makes them prone to Diels–Alder click reactions (D–A) in the presence of a diene precursor. Consequently, one-pot grafting with furfuryl amine onto the graphene sheets, exfoliates pristine graphite resulting in functionalized few-layered graphene which is soluble in organic solvents. Thereafter, the cleavage of the bonds in the adduct can occur by exposure to an external stimulus like temperature, to initiate a retro-Diels–Alder reaction. The success of the thermoreversible functionalization of the few-layered graphene was confirmed by Raman spectroscopy, TGA, XPS, EDX, contact angle and XRD analysis. The morphology of the samples was investigated by scanning electron microscopy and AFM. The latter was utilized to estimate graphene thickness. The results showed that functionalization proceeded under nitrogen with dry ball milling and mild temperatures efficiently.